2021
DOI: 10.4018/ijhcitp.2021070105
|View full text |Cite
|
Sign up to set email alerts
|

Advance Resource Planning in Hospital Emergency Departments Using Machine Learning Techniques

Abstract: Accidents are likely to happen at workplaces which requires employees to rush to the hospitals for emergency treatment. Due to increase in population, treating various medical cases has led to longer waiting times at emergency treatment units (ETUs). The reasons being the ambulance divergence, less staff, and reduced management. An approach to decrease overcrowding at ETU can be the application of modern techniques. Machine learning (ML) is the one which is used to find patients with high illness, therefore de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
0
1
0
Order By: Relevance
“…One similar study by Rawat and Sultana (2021) demonstrates the application of Machine Learning algorithms for advanced resource planning in Hospital Emergency Departments. The authors have developed their model called light gradient boosted machines (LGBM) and found that its accuracy and time taken for prediction is better than other ordinary ML models like decision tree and GBM.…”
Section: Introductionmentioning
confidence: 93%
“…One similar study by Rawat and Sultana (2021) demonstrates the application of Machine Learning algorithms for advanced resource planning in Hospital Emergency Departments. The authors have developed their model called light gradient boosted machines (LGBM) and found that its accuracy and time taken for prediction is better than other ordinary ML models like decision tree and GBM.…”
Section: Introductionmentioning
confidence: 93%
“…However, this paper's fundamental flaw was that it encountered significant problems in task handling operations [22]. Using session data, the implementation of machine learning algorithms for advanced resource planning in hospital emergency departments is demonstrated by [23].…”
Section: Introductionmentioning
confidence: 99%